2011
DOI: 10.1016/j.ejcts.2011.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Partial anomalous pulmonary venous connection to the superior vena cava: the outcome after the Warden procedure

Abstract: The Warden procedure is a safe and effective surgical option for repair of PAPVC to the SVC in terms of preserving the sinus node function and non-obstructive pulmonary venous pathway. However, more attention must be paid to the reconstruction of non-obstructive systemic venous pathway, especially in younger and smaller children. Patch augmentation could be considered and effectively performed, if there is any doubt regarding tension-free anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 21 publications
2
37
1
1
Order By: Relevance
“…However, they did not use the 'RA wall pedicled flap technique.' Park et al [10] reported the use of a modified Warden procedure in 9 cases, with the techniques used in three of these cases being seemingly similar to our technique, for tension-free anastomosis between the cephalic end of the SVC and the RA appendage where the anomalous pulmonary vein enters the more cephalic portion of the SVC. Tao et al [11] reported that one patient from among their series underwent a similar modification as our patients did.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, they did not use the 'RA wall pedicled flap technique.' Park et al [10] reported the use of a modified Warden procedure in 9 cases, with the techniques used in three of these cases being seemingly similar to our technique, for tension-free anastomosis between the cephalic end of the SVC and the RA appendage where the anomalous pulmonary vein enters the more cephalic portion of the SVC. Tao et al [11] reported that one patient from among their series underwent a similar modification as our patients did.…”
Section: Discussionmentioning
confidence: 87%
“…The technique called 'RA wall pedicled flap technique' has been described and clinically used by a few surgeons [10,11,12]. Nakahira et al [12] used a pedicled autologus pericardial flap for anterior augmentation of cavoatrial anastomosis with the expectation of a sufficient channel and tension-free anastomosis growth potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…и коллеги также доказали, что процедура Warden имеет преимущество перед одно-или двуза-платной внутрипредсердной коррекцией: практичес-ки не возникает нарушений ритма, нет обструкции на сформированном соустье правой легочной вены в ле-вое предсердие, но отмечают стеноз в месте сформи-рованного анастомоза между верхней полой веной и ушком правого предсердия в 10% случаев из 30 пациен-тов [10,11]. В НИИ кардиологии прооперировали 22 пациента (12 мальчиков) по методике Warden.…”
Section: Discussionunclassified
“…Therefore, authors generally recommend the Warden procedure to avoid sinus node dysfunction. 7,8) However in recent series transient sinus node dysfunction 9,10,11) and SVC stenosis 11,12) have been reported after Warden procedure. Park, et al have informed that deep stitches to the sinus node and its artery while reconstructing the pulmonary-venous pathway is the possible mechanism for transient sinus node dysfunction after Warden procedure.…”
Section: Discussionmentioning
confidence: 99%